2012
DOI: 10.1515/sg-2012-0004
|View full text |Cite
|
Sign up to set email alerts
|

Chloroplast DNA variation in planted and natural regenerated stands of black locust (Robinia pseudoacacia L.)

Abstract: Black locust (Robinia pseudoacacia L.), native in mountainous regions in USA, is increasing in importance for forestry in many countries as a „multi-purpose tree“ associated with breeding efforts at the family and clonal levels. A few population genetic studies exist with nuclear, codominantly inherited markers. Here we present an additional marker type, the maternally inherited chloroplast haplotypes. The studied material included samples from the natural range and from artificial stands from three European c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…is key to developing further ecological or evolutionary studies (Lawson Handley et al, 2011), little information exists about its genetic diversity and structure in introduced ranges, nor regarding its origin and differentiation from the population sources in North America. The only studies we know of in Europe compared four American populations with sixteen German and Hungarian populations (Liesebach & Schneck, 2012;Liesebach et al, 2004), but although the results suggested a high genetic differentiation among American populations, they were mostly inconclusive.…”
Section: Although Knowledge About the Black Locust's Genetic Diversitymentioning
confidence: 99%
See 1 more Smart Citation
“…is key to developing further ecological or evolutionary studies (Lawson Handley et al, 2011), little information exists about its genetic diversity and structure in introduced ranges, nor regarding its origin and differentiation from the population sources in North America. The only studies we know of in Europe compared four American populations with sixteen German and Hungarian populations (Liesebach & Schneck, 2012;Liesebach et al, 2004), but although the results suggested a high genetic differentiation among American populations, they were mostly inconclusive.…”
Section: Although Knowledge About the Black Locust's Genetic Diversitymentioning
confidence: 99%
“…Although knowledge about the black locust's genetic diversity is key to developing further ecological or evolutionary studies (Lawson Handley et al, ), little information exists about its genetic diversity and structure in introduced ranges, nor regarding its origin and differentiation from the population sources in North America. The only studies we know of in Europe compared four American populations with sixteen German and Hungarian populations (Liesebach & Schneck, ; Liesebach et al, ), but although the results suggested a high genetic differentiation among American populations, they were mostly inconclusive. Modern molecular and statistical tools used in population genetics have proved to be useful for finding the geographic origins of invasive species, complementing or providing a solution to the lack of available historical knowledge (Besnard et al, ; Chown et al, ; Cristescu, ; Hoos, Whitman Miller, Ruiz, Vrijenhoek, & Geller, ).…”
Section: Introductionmentioning
confidence: 99%
“…In comparison with Germany many stands of black locust are of bad quality concerning the stem form and thick branches. The breeding of black locust was focused on the selection of individuals with straight trunks and their vegetative propagation including tissue culture methods (Liesebach et al 2004). Clonal breeding is one of the possibilities to provide material for commercial use (Rédei et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Besides Hungary the black locust breeding and improvement are undertaken in the United States (Bongarten et al 1991(Bongarten et al , 1992, Greece (DiniPapanastasi, Panetsos 2000), Germany (Liesebach et al 2004;Böhm et al 2011), Slovakia (Chalupa 1992), Poland (Kraszkiewicz 2013;Wojda et al 2015), Turkey (Dengiz et al 2010), India (Sharma, Puneet 2006), China (Dunlun et al 1995) and South Korea (Lee et al 2007). …”
mentioning
confidence: 99%
“…Loci and primers used Liesebach and Schneck (2012) applied PCR-RFLP techniques to investigate polymorphisms in a set of populations analyzed previously with isozymes. Mostly using universal primers, they amplified five chloroplast DNA (cpDNA) loci by means of PCR and digested the amplicons with eight restriction enzymes (Table 2).…”
Section: Organelle Dna Markers (Chloroplast (Cp) Dna Mitochondrial (mentioning
confidence: 99%